THE INFLUENCE OF AI VIDEO ON THE SPREAD OF HOAXES ON SOCIAL MEDIA AMONG GENERATION Z IN INDONESIA WITH THE TECHNOLOGY THREAT AVOIDANCE THEORY (TTAT) - Silvia Antana Sukma; Dedy Setiawan (Bulletin of Network Engineer and Informatics, 2026)
The spread of Artificial Intelligence (AI)-generated hoax videos on social media is increasing and potentially influences Generation Z behavior in disseminating false information in Indonesia. This study aims to analyze the effects of perceived threat, safeguard effectiveness, safeguard cost, self-efficacy, and digital literacy on avoidance motivation and their impact on hoax dissemination behavior using the Technology Threat Avoidance Theory (TTAT) approach. This study employed a quantitative method with purposive sampling involving 250 Generation Z respondents in Indonesia. The sample size was determined based on Hair Jr.’s rule of thumb. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived threat, safeguard cost, and self-efficacy have a positive and significant effect on avoidance motivation, while safeguard effectiveness has no significant effect. Avoidance motivation significantly affects hoax dissemination behavior. In addition, digital literacy significantly influences avoidance motivation and hoax dissemination behavior and also has an indirect effect through avoidance motivation as a mediating variable. This study demonstrates that TTAT factors and digital literacy play an important role in shaping Generation Z’s behavior in responding to AI-based hoaxes on social media. The practical implication highlights the importance of improving digital literacy and awareness of AI-generated hoaxes to reduce the spread of false information.